Radiation Therapy for Cutaneous Blastic Plasmacytoid Dendritic Cell Neoplasm: A Case Report and Review of the Literature - Masashi Taka; Shinichiro Toyoshima; Shigeyuki Takamatsu; Satoshi Kobayashi (Current Oncology)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a clinically aggressive hematologic malignancy derived from plasmacytoid dendritic cells. It commonly presents as cutaneous lesions. To date, no standard treatment protocol for BPDCN exists. Traditionally treated similarly to acute leukemia or lymphoma, its prognosis remains poor. Radiation therapy is employed for isolated skin lesions, for patients that are ineligible for chemotherapy due to age or comorbidities and for post-chemotherapy recurrence. However, very limited reports are available on radiotherapy for BPDCN. We present a case involving a 94-year-old BPDCN patient treated with radiation therapy, highlighting an atypical situation of two separate radiotherapy sessions with different dosages for isolated skin lesions. Initially, 45 Gy was administered in 15 fractions (45 Gy/15 Fr), followed by a second session of 30 Gy in 10 fractions (30 Gy/10 Fr) after disease recurrence. This case is unique in detailing radiation therapy for the exceedingly rare BPDCN, particularly dose fractionation. The findings indicate that 45 Gy/15 Fr can provide adequate local control, while even a lower dose of 30 Gy/10 Fr may be effective. This case report contributes to the limited literature by proposing potential therapeutic approaches and dosage guidelines to refine future BPDCN treatment protocols.